Analysis of Students Misconception Using Certainly of Response Index (CRI) in the Periodic System of Elements Concept - Yusran Ramadhan; Kartini Rahman Nisa; Sunarwin Sunarwin (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
This research aimed to investigate the students' understanding level and the occurrence of student's misconceptions about the periodic system of elements subject. Descriptive research with a qualitative approach is a research method used in this study, that is by explaining the data obtained from the result regarding the misconceptions that occur. The technique used in data collection was a test equipped with a choice of the confidence level of answer (TKJ), questionnaires, and interviews. The results showed that the level of understanding experienced by students was still very low, that is 20.2% of students identified as students who misconception about the subject and 8.5% understood the concept and 71.3% of students who did not understand the concept. The factors that caused the misconceptions were the lack of students' initial concepts and the basic abilities of students.